2014
DOI: 10.7860/jcdr/2014/8231.5343
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Approach for the Treatment of Periodontitis by Curcumin

Abstract: Locally delivered 1% curcumin gel was more effective in inhibiting the growth of oral bacteria when used as an adjunct to SRP in the treatment of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…Bhatia et al [30] proved the bactericidal activity of curcumin against P. gingivalis and P. intermedia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatia et al [30] proved the bactericidal activity of curcumin against P. gingivalis and P. intermedia.…”
Section: Discussionmentioning
confidence: 99%
“…Bhatia et al [30] examined that the patients with 1% curcumin gel along with scaling and root planning showed improvements in clinical parameters and reductions in the count of periodontopathic bacteria and were seen after 6 months, comparing with control sites receiving scaling and root planing only. Curcumin was used with scaling and root planing in the treatment of gingivitis and chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Guimarães et al also observed the lack of inhibition of bone resorption in an experimental model of lipopolysacharide (LPS)-induced periodontal disease (76), which is surprising, keeping in mind that curcumin was shown to significantly inhibit Porphyromonas gingivalis LPS-induced TNF-α and IL-1β production (80). Curcumin has also exhibited exhibited bactericidal activity against Porphyromonas gingivalis, Prevotella intermedia, Fusobacterium nucleatum and capnocytophaga at a minimal inhibitory concentration (MIC) of 1 mg/ml by the local application into periodontal pockets in humans (81). The results of the benzoyl-DL-arginine-naphthylamide (BANA) test, which verifyied the presence of Tannerella forsythia, Treponema denticola, Porphyromonas gingivalis and capnocytophaga species, was similar for 1% curcumin solution and 0.2% chlorhexidine gluconate in subgingival irrigation.…”
Section: Changes In the Bodymentioning
confidence: 99%
“…Studies have reported the anti-periodontitis activity of films or other localised oral mucosal or gingival drug delivery systems [18][19][20][21][22][23]. Many studies have reported on the potential of novel ciprofloxacin delivery devices in the treatment of periodontitis [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%